Application of Extractive Fermentation on the Recuperation of Exopolysaccharide from Rhodotorula mucilaginosa UANL-001L - Medina Ramírez, Carlo Franco; Castañeda Guel, Mariana Teresa; Alvarez González, Ma. Fernanda; Montesinos Castellanos, Alejandro; Morones Ramírez, José Rubén; López Guajardo, Enrique A.; Gomez Loredo, Alma Elizabeth (Molecular Diversity Preservation International, 2020)
Exopolysaccharides (EPS) are high molecular weight biomaterials of industrial interest due to their variety of applications in the pharmaceutical, cosmetic, environmental, and food industries. EPS produced by Rhodotorula mucilaginosa UANL-001 L has sparked interest due to its bio-adsorbent and wide spectrum antimicrobial properties. However, full exploitation and commercial application of EPS has been restrained due to low yields and high production costs. In the present work, the production and separation of EPS from Rhodotorula mucilaginosa UANL-001L was attempted through extractive fermentation in order to increase EPS production while simplifying the recovery process. Extractive fermentation was implemented with a thermoseparating polymer for phase formation (EOPO 970 and EOPO 12,000); culture viability, biomass generation, EPS production, rheological system properties, and phase formation time and temperature were monitored throughout the process. Extractive fermentation of Rhodotorula mucilaginosa UANL-001L with EOPO 970 resulted in a 42% EPS and 7% biomass recovery on the top phase after 5 to 13-min phase formation time and temperatures between 30 and 40 °C. This is the first report of extractive fermentation application for EPS production by yeast of the genera Rhodotorula, resulting in an interesting strategy for EPS production and recovery, although further optimization is needed.